Analysis of problems in the DNSSEC automation deployment - Chuan GUO; Feng LENG (网络与信息安全学报)
Based on the practice of domain name system security extensions protocols' deployment in country code top-level domain,the development background of the domain name system security extensions protocols were summarized,the current applications of the domain name system security extensions protocols were analyzed,the automation problems in the domain name system security extensions protocols' deployment were put forward and analyzed,several issues that need to be addressed when deploying the domain name system security extensions protocols in the production environment were summarized and analyzed.